Structure of Infectious Bursal Disease Virus - Hirai, K. (1974)
Infectious bursal disease virus of chickens was purified, and its structure was examined by the negative-staining technique in the electron microscope. The buoyant density of infectious bursal disease virus in CsCl was found to be 1.34 g/cm(3). The morphological details suggest that the capsid of the virion consists of a single layer of 32 capsomeres arranged in 5:3:2 symmetry. The virion measured about 55 nm in diameter and had no envelope.